Strategy-Proof Package Assignment - Albin Erlanson; Karol Szwagrzak (Lund University, School of Economics and Management, Department of Economics, 2013)
We examine the strategy-proof allocation of multiple divisible and indivisible resources; an application is the assignment of packages of tasks, workloads, and compensations among the members of an organization. We find that any allocation mechanism obtained by maximizing a separably concave function over a polyhedral extension of the set of Pareto-efficient allocations is strategy-proof. Moreover, these are the only strategy-proof and unanimous mechanisms satisfying a coherence property and responding well to changes in the availability of resources. These mechanisms generalize the parametric rationing mechanisms (Peyton Young, 1987, Mathematics of Operations Research 12 (3), 397-414.), some of which date back to the Babylonian Talmud.
Keywords: C70; D47; D61; D63; D70; 330; Package assignment; Indivisible objects; Strategy-proofness